Usage of bioactivated PCL nanofiber as a fluoxetine capturing matrix in milk - AKBAY, TUĞBA (TAYLOR & FRANCIS INC, 2020)
In this study, for the first time, polycaprolactone (PCL) nanofiber matrix was bioactivated for the removal of fluoxetine from milk. Bioactivated nanofiber was prepared by immobilizing fluoxetine antibody on PCL nanofiber matrix. The fluoxetine removal efficiency of bioactivated nanofiber in milk was found to be approximately 93.6%. This removal did not significantly change the biochemical composition of milk. In conclusion, as a novel product, bioactivated nanofibrous PCL matrix can be used for the removal of drugs or unwanted chemicals from breast milk or from other fluids.
Keywords: Fluoxetine; polycaprolactone; nanofiber; milk; ANTIBODIES; IMMOBILIZATION; DELIVERY; DRUG